Identifikasi Minat Belajar Kelas XI Dan XII SMA Negeri 6 Muaro Jambi Pada Pembelajaran Fisika - Novri Hutauruk; Erika Erika (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
This research was conducted with the aim to find out the description of the attitude of interest in learning towards physics possessed by students in SMA Negegi 6 Muaro Jambi. The design of this research is quantitative research with the instrument used is a questionnaire. The population of this study is 6 Muaro Jambi Public High School and the sample taken is Muaro Jambi 6 Public High School students. Data analysis was performed using the SPSS Application. From this study it can be said that students in Muaro Jambi 6th High School XI and XII have a good interest in learning about Physics, which is as much as 46%.